BUTLER MATRIX IN MICROSTRIP-SLOT TECHNOLOGY - Rajeswari, D.; Jayanthy, T. (International Journal of Research -GRANTHAALAYAH, 2017)
The design of a 4 x 4 Butler Matrix for use in a multi-beam antenna array operating over wide frequency band is presented. In order to achieve wideband characteristics, the matrix uses microstrip-slot technology that employs two microstrip dielectric layers with a common ground plane and a coupling slot. The designed Butler matrix is compact in size and does not use crossovers. Its prototype is manufactured. The performance of the designed device is assessed via full-wave electromagnetic simulations and measurements.